Following the olive oil production chain: 1D and 2D NMR study of olive paste, pomace, and oil. Issue 11 (15th July 2014) - Del Coco, Laura; De Pascali, Sandra Angelica; Iacovelli, Vito; Cesari, Gianluigi; Schena, Francesco Paolo; Fanizzi, Francesco Paolo
<x xml:space="preserve">Abstract</x> Extraction methods are critical in the production and success of an extra virgin olive oil ready for consumption. The first step of olive oil extraction procedure produces an olive paste, which is subsequently processed by separation of the liquid phases (oil and vegetable water) from the pomace. Profiles of Apulian extra virgin olive oils and the deuterated chloroform extracts of its paste and pomace were studied by 1D and 2D NMR (NMR) spectroscopy without separation and pre‐treatment of samples. In order to study the metabolic profiles variation in the paste and pomace extracts with respect to the corresponding EVOOs, multivariate statistical analyses (PCA and OPLS DA) of the 1H NMR data were performed. As expected, a different minor components profile, in particular for the presence of higher content of secoiridoids, lignans and phenolic compounds in olive paste and pomace extracts with respect to the EVOOs, was observed. Practical applications: Amount of extractable oil from olive paste and pomace after the production processes of EVOO was measured by 1H NMR spectroscopy. Identification of metabolites in olive paste and pomace was performed by 1D and 2D NMR spectroscopy without separation and pre‐treatment of samples. The chemical composition of major and minor components (in particular secoiridoids, lignans, and phenolic compounds) present in olive paste and pomace chloroform extracts could be used for extraction process trimming purposes as well as in fingerprint analyses for cultivar and/or geographical origin certification of olive oil production. Moreover, determination of the entire metabolic content of different materials of the olive oil production process could be exploited in other applications such as recycling on agricultural land, studies of the health benefits on human nutrition and alternative dietary lipid source in animals. In fact, it is worth noting that the olive paste and pomace extracts could be even healthier than other vegetable oils. <inline-graphic xlink:href="ark:/27927/pgh2cj8kvd4" content-type="ejlt201400139-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> The extraction processes are critical in the extra virgin olive oil production. The chemical composition of EVOOs and its paste and pomace extracts have been investigated by Nuclear Magnetic Resonance Spectroscopy (NMR).